Details of the Peasants Everyday Life in the Grand Duchy of Lithuania in the 16th Century and the First Half of the 17th Century - Dambrauskaitė, Neringa (Lietuvos istorijos studijos, 2020)
This article deals with the aspects of everyday life of the peasants who lived in private estates of the nobility in the Grand Duchy of Lithuania in the 16th – the first half of the 17th century. The research was mainly based on published and unpublished acts of court cases, additional information is found in the estate inventories and descriptions provided by the people who travelled through Lithuania. The analysis revealed that the homestead of the peasants were usually modest – it consisted of few wooden buildings, the most important of which being a dwelling house, a granary and a cattle-shed, but richer peasants lived in larger homesteads with more different buildings. Peasants usually lived in wooden farmhouses with a stove, whereas some part of the peasants in Samogitia still lived in the so-called numas with a fireplace. Peasants’ main clothes were sermėgos, sheepskin coats, shirts, woman’s cloaks; some peasants could afford to have more expensive clothes. The main food products included different kinds of grain, first of all, stocks of rye, as well as peas, different vegetables, flitch, dairy products. Probably only richer peasants ate meat more often. There were important various household effects and work tools in the peasant homestead. Although the life of peasants was modest, however there existed differences in the standard of everyday living during the period under discussion.
Keywords: peasants; Grand Duchy of Lithuania; everyday life; material environment; nutrition; clothing